Magnetic Resonance Imaging Evaluation of Closed-Mouth TMJ Disc-Condyle Relationship in a Population of Patients Seeking for Temporomandibular Disorders Advice. (2nd December 2021) - Tresoldi, Matteo; Dias, Ricardo; Bracci, Alessandro; Segù, Marzia; Guarda-Nardini, Luca; Manfredini, Daniele
Abstract : Objective . To characterize the closed-mouth temporomandibular joint (TMJ) disc-condyle relationship in a population of individuals who sought hospital services for temporomandibular disorders (TMD). Methods . Two hundred and twenty-four TMJ magnetic resonance images (MRIs) of 112 patients were assessed in all spatial planes to classify disc position with respect to the condyle in a closed-mouth position. Results . Disc displacement (DD) was present in 62.1% and superior disc position in 29.9% of the patients. Position could not be determined in 8% of the cases. Among DD, pure anteriorized position was the most common condition (34.4%), with different combined translational and rotational displacements in all the other joints (27.7%). Conclusion . There is a wide biological variability in disc position in closed mouth among patients seeking for TMD advice. Getting deeper into the correlation with clinical symptoms is recommended to refine the potential relevance of any diagnostic and management strategies based on the imaging evaluation of TMJ disc position.